Essential oil composition and antioxidant, anticancer activities of Rhodiola rosea L. grown in Mongolia - J, Irekhbayar; S, Shatar; Sh, Altantsetseg (Bulletin of the Institute of Chemistry and Chemical Technology, 2018)
Essential oil plants have been used for a long time in traditional medicine. Rhodiola rosea L., also called “roseroot”, is a common member of the family Crassulaceae, known as one of the most important popular medicinal plants in the northern region of Europe. The roots of R.rosea possess a wide range of pharmacological activities such as antioxidant, antiinflammatory, anti-cancer, cardioprotective, and neuroprotective effects that are because of the presence of different phytochemicals such as phenols and flavonoids. The chemical composition of essential oil from R.rosea was determined by GC/MS analysis. The essential oil of R.rosea mainly consists of oxygenated monoterpenes (83.38 %). The chief components of the oil were geraniol (25.93 %), myr-tenol (14.94 %), octanol (13.71 %) and (E)-pinocarveol (11.07 %). Antioxidant activity of ethanol extract (root) was evaluated by using DPPH (1,1-diphenyl-2-picrylhydrazine) radical scavenging assay with an IC50 value of 5.84 μg/ml. The cytotoxicity was measured using the MTT assay. The ethanol extract of R.rosea pre-sented toxic activity against A-431 (51.80%) human epidermoid carcinoma cell line. Монгол орны Ягаан мүгэз (Rhodiola rosea L.) ургамлын эфирийн тосны химийн бүрэлдэхүүн, исэлдэлт ба хавдрын эсрэг идэвхийн судалгаа Хураангуй: Эфирийн тост ургамлууд нь уламжлалт анагаах ухаанд олон зууны турш хэрэглэгдсээр ирсэн. Ягаан мүгэз (Rhodiola rosea L. – Алтан хөлт, Алтан гагнуур) ургамал нь Зузаалайн овгийн ургамал бөгөөд Европын хойт бүсийн нутагт хамгийн чухал эмийн ургамалд тооцогддог. Ягаан мүгэз ургамлын үндэс нь исэлдэлт, үрэвсэл болон хавдрын эсрэг зэрэг фармакологийн идэвхтэй бөгөөд фенол ба флавоноид зэрэг нэгдлүүд нь зүрх судас болон мэдрэлийн системийн үйл ажиллагааг хамгаалах үйлчлэлтэй. Ягаан мүгэз ургамлын эфирийн тосны химийн найрлагыг хийн хроматограф-масс спектроскопийн аргаар тодорхойлоход монотерпеноидууд (83.3%) ихэнх хэсгийг эзэлж байв. Үүнээс гераниол (25.93%), миртенол (14.94%), октанол (13.71%) ба (E)-пинокарвеол (11.07%) зэрэг нь голлох нэгдлүүд байв. Исэлдэлтийн эсрэг идэвхийг DPPH (1,1-дифенил-2-пикрилгидразин) аргаар судлахад чөлөөт радикалыг дарангуйлах IC50 5.84 μг/мл байгаа нь тогтоогдов. Хорт хавдрын эсийн ургалтыг дарангуйлах идэвхийг МТТ аргаар тодорхойлоход Ягаан мүгэз ургамлын үндэсний этанолын ханд хүний ходоодны хорт хавдрын эс А-431эсийн ургалтыг илүү сайн (51.80%) дарангуйлж байв. Түлхүүр үгс: Алтан гагнуур, эфирийн тос, исэлдэлт ба хавдрын эсрэг идэвх